Visible-light-driven nanoscale zero-valent iron loaded rGO/g-C3N4 for fluoroquinolone antibiotics degradation in water - Liu, Chen; Xie, Yuqian; Jiao, Yuzhu; Du, Yongjuan; Zheng, Qinmin; Sun, Yingxue (Frontiers in Environmental Science, 2022)
Fluoroquinolone antibiotics attract increasing attention in the water treatment field because of the potential adverse effects on aquatic ecosystems and human health. The graphitic carbon nitride (g-C3N4) based photocatalysis has been demonstrated as an economically feasible and environmentally benign process to control these persistent contaminants. In this study, a new visible-light-driven of reduced graphene oxide (rGO) and nanoscale zero-valent iron (nZVI) co-modified g-C3N4-based photocatalyst was synthesized via ultrasonication-assisted chemisorption method. The optimized nZVI-loaded rGO/g-C3N4 (10%IGCN) showed a reaction rate enhancement of 2.12~3.69-fold and 1.20~1.68-fold for the degradation of ofloxacin (OFL), norfloxacin (NOR), and ciprofloxacin (CIP) compared to that of carbon-doped g-C3N4 (MCB0.07) and rGO-supported g-C3N4 (7.5%GCN) under the irradiation of simulated visible light, respectively. The enhanced photocatalytic activity can be ascribed to the synergistic effect of nZVI and rGO to improve the separation of charge carriers and boost the harvest of visible light. The degradation mechanisms were explored by scavenger tests and X-ray photoelectron spectroscopy (XPS), indicating that holes (h+) played a dominant role in the decomposition of OFL, NOR, and CIP. The piperazine ring and C－N between the piperazine ring and benzene were the primary attack sites of h+. In addition, the ring-opening oxidation of benzene (C＝C bond) connected by the C－F bond may also be an essential step. This study shed light on the degradation mechanism of OFL, NOR, and CIP under visible light irradiation of the 10%IGCN and provided theoretical support for the practical application of photocatalysis in treating antibiotics-containing water.